Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1055/s-0035-1565268
|View full text |Cite
|
Sign up to set email alerts
|

A Homozygous TPO Gene Duplication (c.1184_1187dup4) Causes Congenital Hypothyroidism in Three Siblings Born to a Consanguineous Family

Abstract: Congenital hypothyroidism (CH) is the most common neonatal endocrine disease, and germ-line mutations in the TPO gene cause the inherited form of the disease. Our aim in this study was to determine the genetic basis of congenital hypothyroidism in three affected children coming from a consanguineous Turkish family. Because CH is usually inherited in autosomal recessive manner in consanguineous/multicase families, we adopted a two-stage strategy of genetic linkage studies and targeted sequencing of the candidat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 28 publications
(32 reference statements)
0
1
0
Order By: Relevance
“…At present, the genetic mechanisms underlying hypothyroidism pathogenesis remain poorly understood. It has been reported that the c.1184_1187dup4 mutation in the thyroid peroxidase gene, c.40A>G and c.94G>A mutations in the thyroid-stimulating hormone β gene, p.G488R, p.A649E, p.R885Q, p.I1080T and p.A1206T mutations in the dual oxidase 2 gene, and the p.Y138X mutation in the dual oxidase maturation factor 2 gene are associated with congenital hypothyroidism ( 25 27 ). WES technology is an effective method for identifying potential causative genes in disease phenotypes.…”
Section: Discussionmentioning
confidence: 99%
“…At present, the genetic mechanisms underlying hypothyroidism pathogenesis remain poorly understood. It has been reported that the c.1184_1187dup4 mutation in the thyroid peroxidase gene, c.40A>G and c.94G>A mutations in the thyroid-stimulating hormone β gene, p.G488R, p.A649E, p.R885Q, p.I1080T and p.A1206T mutations in the dual oxidase 2 gene, and the p.Y138X mutation in the dual oxidase maturation factor 2 gene are associated with congenital hypothyroidism ( 25 27 ). WES technology is an effective method for identifying potential causative genes in disease phenotypes.…”
Section: Discussionmentioning
confidence: 99%